Trend followers, contrarians and fundamentalists: Explaining the dynamics of financial markets - Noemi Schmitt; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2019)
We propose an empirically motivated financial market model in which speculators rely on trend-following, contrarian and fundamental trading rules to determine their orders. Speculators' probabilistic rule-selection behavior - the only type of randomness in our model - depends on past and future performance indicators. For a large number of speculators, the model's intrinsic noise vanishes and its dynamics is driven by an analytically tractable nonlinear map. An in-depth investigation into this map provides the key to understanding how the model functions. Since our model is able to match a number of important stylized facts concerning financial markets, it may be regarded as validated.
Keywords: C63; D84; G15; 330; financial markets; stylized facts; technical and fundamental analysis; probabilistic rule-selection behavior; nonlinear dynamics; stability and bifurcation analysis